Estudo de genótipos para características de milho verde sob diferentes níveis de nitrogênio, em Buri - SP - Ferreira, Maria Eduarda de Oliveira (Universidade Federal de São Carlos, 2021)
The objective of this study was to study genotypes from open populations and non-transgenic commercial corn genotypes (Zea mays L.), in the search to know the most efficient populations for nitrogen use under conditions of low and high N supply in cover (30 and 160 kg ha1 of N) in the production of green corn, at experimental area of the Federal University of São Carlos - Lagoa do Sino Campus, located at municipality of Buri- SP, in the 2019 crop. The experimental design used was randomized block design, with three repetitions and two doses. Variables of agronomic and commercial interest for green corn production were evaluated: plant height, first ear insertion height, length and diameter of ear without straw, and green mass of ear without straw. Analyses of variance and Scott-Knott test were performed for all characteristics. There was no statistically significant difference for any characteristic in relation to nitrogen doses. All variables showed significant differences in relation to the genotype, showing its importance for this study, being possible to notice that in the F3 generation (open population genotypes) showed good performance for green corn, when compared to commercial genotypes
Study of genotypes for characteristics of green corn under different nitrogen levels, at Buri - SP
Keywords: Zea mays L.; População aberta; Adubação nitrogenada; Open population; Nitrogen; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA